An investigation of olfactory bulb and entorhinal cortex volumes in both patients with Alzheimer's disease and healthy individuals, and a comparative analysis of neuropeptides - Kaptan, Zülal; Burakgazi, Gülen; Ünalmış, Demet; Petekkaya, Emine; Kuş, Berna; Arpacı, Abdullah; Melek, İsmet Murat (ScopeMed, 2020)
Alzheimers Disease (AD) is the most common neurodegenerative disease and is hard to diagnose at the early stages. The pathogenesis of AD is associated with the loss of a sense of smell. Reduction in the volumes of the Olfactory Bulb (OB) and Entorhinal Cortex (EC) is positively correlated with the decline of the smelling function where OB projects to EC. This study aims to detect the early changes in OB and EC volumes in AD patients by comparing them to healthy subjects. This study also aims to make a comparative analysis of plasma levels and the relationship between arginine-vasopressin (AVP) and Oxytocin (OT), which are neuropeptides associated with cognitive functions. The participants comprised 9 AD patients and 12 healthy individuals. We used volumetric methods such as MRICloud and IBASPM to measure the OB and EC volumes with the help of 3D MRI (Magnetic Resonance Imaging) images. We compared the left and right differentiation. Moreover, we investigated the neuropeptide levels in blood samples from the participants. We conducted a correlation analysis for all parameters. Bilateral OB atrophy was discovered in the AD patients in comparison to the control group (p=0.002 for right; p=0.015 for left). The right OB volume was measured to be larger than the left OB volume in the control group,but this asymmetry was not observed in the AD patients. The right and left EC's of the AD patients were atrophic in comparison to the control (p [Med-Science 2020; 9(4.000): 866-71]
Keywords: arginin vasopressin; entorhinal cortex; olfactory bulb; oxytocin; R; alzheimer's disease; Medicine; 3. Good health